FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BEI - Elyn Mareni; Merry Susanti (Jurnal Paradigma Akuntansi, 2023)
This research aimed to test the effects of profitability, liquidity, assets growth, and sales growth on capital structure. The objects of this research were manufacturing companies listed on the Indonesian Stock Exchange for the period 2017-2019. This study using purposive sampling method and valid data was 35 companies. The method in this study using multiple regression analysis assisted by Eviews statistical tool version 11. The results showed that profitability and liquidity had a negative effect on capital structure. Furthermore, assets growth and sales growth did not have significant effect on capital structure.